Mild Hypokalemia and Supraventricular Ectopy Increases the Risk of Stroke in Community-Dwelling Subjects. Issue 3 (March 2017) - Mattsson, Nick; Kumarathurai, Preman; Larsen, Bjørn Strøier; Nielsen, Olav Wendelboe; Sajadieh, Ahmad
Abstract : Background and Purpose—: Stroke is independently associated with the common conditions of hypokalemia and supraventricular ectopy, and we hypothesize that the combination of excessive supraventricular ectopic activity and hypokalemia has a synergistic impact on the prognosis in terms of stroke in the general population. Methods—: Subjects (55–75 years old) from the Copenhagen Holter Study cohort (N=671) with no history of atrial fibrillation or stroke were studied—including baseline values of potassium and ambulatory 48-hour Holter monitoring. Excessive supraventricular ectopic activity is defined as ≥30 premature atrial complexes per hour or any episodes of runs of ≥20. Hypokalemia was defined as plasma-potassium ⩽3.6 mmol/L. The primary end point was ischemic stroke. Cox models were used. Results—: Hypokalemia was mild (mean, 3.4 mmol/L; range, 2.7–3.6). Hypokalemic subjects were older (67.0±6.94 versus 64.0±6.66 years; P <0.0001) and more hypertensive (165.1±26.1 versus 154.6±23.5 mm Hg; P <0.0001). Median follow-up time was 14.4 years (Q1–Q3, 9.4–14.7 years). The incidence of stroke was significantly higher in the hypokalemic group (hazard ratio, 1.84; 95% confidence interval, 1.04–3.28) after covariate adjustments, as well as in a competing risk analysis with death (hazard ratio, 1.51; 95% confidence interval, 1.12–2.04). Excessive supraventricular ectopic activity was also associated with stroke (hazard ratio, 2.23; 95% confidence interval, 1.33–3.76). The combination of hypokalemia and excessive supraventricular ectopic activity increased the risk of events synergistically. Stroke rate was 93 per 1000 patient-year ( P <0.0001) in this group (n=17) compared with 6.9 (n=480); 11 (n=81), and 13 (n=93) per 1000 patient-year in the groups without the combination. Conclusions—: The combination of hypokalemia and excessive supraventricular ectopy carries a poor prognosis in terms of stroke. Abstract : Supplemental Digital Content is available in the text.